Fungsi Seni Teater sebagai Media Kritik Sosial dalam Cerita Rakyat Ã¢â‚¬Å“Putri MandalikaÃ¢â‚¬Â - Desnayanti, Rosita; Kailani, Ashwan (Universitas Hamzanwadi, 2019)
This research aims to know the presentation form of Putri Mandalika theater and function of Putri Mandalika theater as a medium of social criticism. This research is descriptive qualitative research. The theory of social criticism as a tool to dissect social relationship that occur because of the forms and rules of life that are caused by humans.The research has ben conducted in Seriwe village, Jerowaru district and the presentation theater of Putri Mandalika. Data collection techniques used by research is observation, interview and documentation. Data analysis technique in this research is data reduction, data display and conclusion drawing. After data analysis, it can be concluded that: (a) The form presenting of Putri Mandalika theater uses a different concept that has been modified. (b) Putri Mandalika theater can be a media of social criticism.